SHM-based practical safety evaluation and vibration control model for steel pipes - Bae, Sang Geun; Choi, Jewoo; Kang, Deok Shin; Hong, Taehoon; Lee, Dong-Eun; Park, Hyo Seon (Journal of Civil Engineering and Management, 2023)
Unexpected damages or failures of steel pipes in refineries cause significant disruption to economic activity. While research has been conducted on the prevention of damage to steel pipes, no systematic methods or practical techniques for monitoring of vibrations to estimate the state of pipeline system have been reported. In this study, vibration safety evaluation model consisting of design – evaluation – control steps was developed to measure and control the vibration level during operation of the piping system of an oil refinery. The measurement location was designed by examining the structure of the pipe, and the vibration level measured at each location was compared with the allowable vibration level. Subsequently, two types of vibration reduction measures, namely, dynamic absorbers and viscous dampers, were introduced to reduce the vibration level. The effect of the application of the monitoring system was evaluated by comparing the vibration levels of the steel pipes before and after the application of the dynamic absorbers and viscous dampers. The vibrations of steel pipes in the oil refinery during operation decreased by over 50%. Upon applying the dynamic absorbers and viscous dampers, the responses of the frequency component also exhibited local and global reductions of approximately 50–80%.